The meteoritical bulletin, No. 94 - Weisberg, M.; Smith, C.; Benedix, Gretchen; Folco, L.; Righter, K.; Zipfel, J.; Yamaguchi, A.; Aoudjehane, H. (John Wiley & Sons, Inc., 2008)
The Meteoritical Bulletin 94 reports over 900 (119 non-Antarctic and 803 Antarctic) newly approved meteorite names and their recovery histories, macroscopic descriptions, petrography, mineral compositions, and geochemistry. Meteorites reported include lunar, Martian, howardites, eucrites, diogenites, mesosiderites, aubrites, irons, angrites, ureilites, acapulcoites, lodranites and H, L, LL, R, CO, and CV chondrites. Eight of the meteorites in this bulletin are falls, including 4 from India (Jodiya, Kaprada, Kavapura, Mahadevpur), 1 from Mali (Chergach), Turkey (Didim), Libya (Werdama), and the U.S. (Berthoud).